The Influence of Individual Factors and Individual Behavior on Employee Performance at PT. Naga Aries Teknologi - Firda Mufaricha Octavia; Pompong B Setiadi; Sri Rahayu (Departement of Mathematics Education, 2023)
This study aims to analyze the influence of individual factors and individual behavior on employee performance at PT. Naga Aries Teknologi Surabaya. The research is aimed to employees of PT. Naga Aries Teknologi. Research respondents amounted to 45 people with the type of research sample selection, namely the sampling method in this study using saturated sampling techniques. Saturated sampling is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small. The research method used is a survey using questionnaire with reference to the Likert scale and type of research is exploratory research. Methods of data analysis using multiple linear regression, hypothesis testing and coefficient of determination. The data processing stage uses IBM Version 25 Statistical Application Solution (SPSS). The results showed that simultaneously, individual factors and individual behavior simultaneously influence the performance of PT. Naga Aries Teknologi. It can be said that individual factors and well-executed individual behavior can improve the performance of PT. Naga Aries Teknologi